Analysis of Socio-economic Attributes of MGNREGA Beneficiaries in Nagaland with Special Reference to Employment Generation and Community Empowerment - Longchar, Tiajungla; Longkumer, J. (International Journal of Bio-resource and Stress Management, 2012)
A study was carried out in Mon district of Nagaland (India) to find out the socio-economic characteristics of the MGNREGA (Mahatma Gandhi National Rural Employment Guarantee Act) beneficiaries and to explore the relationship between selected economic parameters of the beneficiaries and employment generation and community empowerment. A total of 120 respondents were selected randomly from six villages under Mon rural development block. The analyses of socio-economic and individual characteristics of the respondents showed that majority of the respondents were under the age group of 33-57 years. Majority (50-67%) of the beneficiaries were male. The respondents were mostly middle school educated. Nearly 45% had medium size land holding. Houses were mostly kutcha (earthen) type. They had low annual income with little or no savings. However, the saving habit of the people improved marginally after the program owing to additional income generation. Employment generation was found to have positive and significant relationship with annual income (r=0.299) and awareness about MGNREGA (r=0.250). On the other hand, community empowerment was found to have negative and significant relationship with age (r=-0.258). The study showcased a good coverage of the program in the study area, having provided job cards to all households. The socio-economic progress of the beneficiaries through MGNREGA in the study area was thus, found to be quite encouraging especially in promoting the income level and savings habit.